2009
DOI: 10.1182/blood-2009-01-202028
|View full text |Cite
|
Sign up to set email alerts
|

Copy number abnormalities, MYC activity, and the genetic fingerprint of normal B cells mechanistically define the microRNA profile of diffuse large B-cell lymphoma

Abstract: MicroRNA (miRNA) deregulation contributes to cancer pathogenesis. However, analysis of miRNAs in diffuse large B-cell lymphoma (DLBCL) has been hindered by a focus on cell lines, limited number of miRNAs examined, and lack of copy number data. To address these restrictions, we investigated genomewide miRNA expression and copy number data in 86 DLBCLs. Permutation analysis showed that 63 miRNAs were recurrently disrupted in DLBCL, including highly expressed oncomirs not previously linked to chromosomal abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
79
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 45 publications
(70 reference statements)
1
79
0
Order By: Relevance
“…Recently, Li et al identified 16 microRNAs that could effectively discriminate DLBCL into 3 unique subgroups that were unrelated to GC/ABC classifications (44). These authors were unable to distinguish GC-and ABC-like subgroups in 53 primary DLBCL tumours using the Malumbres 9 microRNA signature (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Li et al identified 16 microRNAs that could effectively discriminate DLBCL into 3 unique subgroups that were unrelated to GC/ABC classifications (44). These authors were unable to distinguish GC-and ABC-like subgroups in 53 primary DLBCL tumours using the Malumbres 9 microRNA signature (44).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Li et al identified 16 microRNAs that could effectively discriminate DLBCL into 3 unique subgroups that were unrelated to GC/ABC classifications (44). These authors were unable to distinguish GC-and ABC-like subgroups in 53 primary DLBCL tumours using the Malumbres 9 microRNA signature (44). By contrast, more recently, Lawrie et al using clinical samples have identified a discriminatory signature (23) that includes microRNAs which they previously reported as discriminatory (21), which correctly predicted lymphoma subtype and disease outcome (23).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, the MYC oncogene has been recently shown to upregulate the expression of the miR-17-92 cluster and emerged as a key regulator of the miRNA profile in DLBCL. 20 In humans, chromosomal amplification at 13q31-q32 leads to the cluster's miRNAs overexpression (the chromosome 13 open reading frame 25 gene; C13orf25) in several BCLs, including DLBCL and high-grade FL. [48][49][50] The biological importance of the miR-17-92 cluster is further underlined by the presence of its paralogs on chromosomes 7 and X: these miRNAs, located in different chromosomes, derive from a unique gene that underwent a series of dysregulations (duplications, mutations, and loss) during the early evolution of vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Copy number abnormalities, MYC activity, and the genetic fingerprint of normal B cells mechanistically define the miRNA profile of DLBCL. 20 Among others, several miRNAs of the miR-17-92 cluster have been demonstrated to be the most promising. [17][18][19][20] The miR-17-92 cluster, located at chromosome locus 13q31.3, consists of six miRNAs (miR-17, miR-18a, miR-19a, miR-20a, miR-19b, and miR-92a) and two paralogs (the miR-106b-25 cluster on chromosome 7 and the miR-106a-363 cluster on chromosome X).…”
mentioning
confidence: 99%
See 1 more Smart Citation